2017
DOI: 10.1371/journal.pone.0186463
|View full text |Cite
|
Sign up to set email alerts
|

Reduced resting state connectivity and gray matter volume correlate with cognitive impairment in minimal hepatic encephalopathy

Abstract: Background and aimsMinimal hepatic encephalopathy (MHE) is associated with cognitive alterations and changes in connectivity. We assessed the relationship of the abnormalities of resting-state functional connectivity (rs-FC) and gray matter (GM) volume with different cognitive alterations and biochemical parameters associated to MHE.MethodsThirty-nine cirrhotic patients (26 without and 13 with MHE) and 24 controls were widely cognitive assessed with a battery of psychometric tests. Atrophy was determined using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
4
16
0
Order By: Relevance
“…Relevant functional networks, such as the DMN and attention networks, the visual network, and thalamo-cortical circuits, are disturbed in cirrhotic patients 27 34 . Patients with MHE show a significant decrease in gray matter volume and reduced functional connectivity in different networks related to attention and executive functions, compared to controls and patients without MHE 24 , 27 29 , 33 .…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Relevant functional networks, such as the DMN and attention networks, the visual network, and thalamo-cortical circuits, are disturbed in cirrhotic patients 27 34 . Patients with MHE show a significant decrease in gray matter volume and reduced functional connectivity in different networks related to attention and executive functions, compared to controls and patients without MHE 24 , 27 29 , 33 .…”
Section: Introductionmentioning
confidence: 91%
“…Magnetic resonance imaging (MRI) makes it possible to study the neuroanatomical and functional changes associated with pathologies such as MHE, and associate these changes with specific cognitive deficits, such as alterations in memory. A significant decrease in gray matter density in several brain areas has been described in cirrhotic patients 23 , 24 . In previous studies, we found a reduction in hippocampus volume in MHE patients compared to healthy controls 24 , 25 .…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…On the other hand, hepatic encephalopathy (HE) is a metabolic neuropsychological syndrome mainly developed from chronic liver disease which usually leads to liver cirrhosis. Altered brain structure in cirrhotic patients has already been reported in many studies ( Chen et al, 2012 ; Garcia-Garcia et al, 2017 ; Zhang et al, 2012 ). Most of these studies focused on the grey matter change in the cortex and striatum, while only one study investigates the relationship between structural changes in thalamus and cirrhotic symptoms ( Tao et al, 2013 ).…”
Section: Introductionmentioning
confidence: 64%